Improved medical student perception of ultrasound using a paired anatomy teaching assistant and clinician teaching model. Issue 2 (17th August 2017) - Smith, Jacob P.; Kendall, John L.; Royer, Danielle F.
Abstract : This study describes a new teaching model for ultrasound (US) training, and evaluates its effect on medical student attitudes toward US. First year medical students participated in hands‐on US during human gross anatomy (2014 N  = 183; 2015 N  = 182). The sessions were facilitated by clinicians alone in 2014, and by anatomy teaching assistant (TA)‐clinician pairs in 2015. Both cohorts completed course evaluations which included five US‐related items on a four‐point scale; cohort responses were compared using Mann‐Whitney U tests with significance threshold set at 0.05. The 2015 survey also evaluated the TAs (three items, five‐point scale). With the adoption of the TA‐clinician teaching model, student ratings increased significantly for four out of five US‐items: "US advanced my ability to learn anatomy" increased from 2.91 ± 0.77 to 3.35 ± 0.68 ( P  < 0.0001), "Incorporating US increased my interest in anatomy" from 3.05 ± 0.84 to 3.50 ± 0.71 ( P  < 0.0001), "US is relevant to my current educational needs" from 3.36 ± 0.63 to 3.54 ± 0.53 ( P  = 0.015), and "US training should start in Phase I" from 3.36 ± 0.71 to 3.56 ± 0.59 ( P  = 0.010). Moreover, more than 84% of students reported that TAs enhanced their understanding of anatomy (mean 4.18 ± 0.86), were a valuable part of US training (mean 4.23 ± 0.89), and deemed the TAs proficient in US (mean 4.24 ± 0.86). By using an anatomy TA‐clinician teaching team, this study demonstrated significant improvements in student perceptions of the impact of US on anatomy education and the relevancy of US training to the early stages of medical education. Anat Sci Educ 11: 175–184. © 2017 American Association of Anatomists.